The armored heart: Differentiating the etiology of hemopericardium on postmortem computed tomography. (June 2017) - Mychajlowycz, Mirek
Highlights: Ante- and post-mortem hemopericardium can be distinguished on postmortem CT (PMCT). The hyperdense armored heart (HAH) suggests pericardial effusion and tamponade. HAH requires further formal characterization in the literature. PMCT is an alternative to evaluate cause and manner of death without autopsy.